CRITICAL INCIDENT STRATEGY: IMPROVING MOTIVATION AND LEARNING OUTCOMES OF ISLAMIC EDUCATION STUDENTS IN PATTANAKARNSUKSA SCHOOL SONGKHLA THAILAND - Fareezee Rattanayium; Asrori Asrori; Rusman Rusman (Universitas Islam Madura, 2023)
Critical Incident Strategy: Increasing Motivation and Learning Outcomes of Islamic Education Students is a strategic issue to be studied in depth through the research process. The method used in this research is PTK with 33 students as subjects. This research consists of 2 cycles in it with motivational targets in cycle 1 and cycle 2, namely student motivation in the medium and high categories, while on learning outcomes, namely the minimum class criterion value in cycle 1 is 65, cycle 2 is 75. The results of the study show, with critical incident strategy, obtained motivation and learning outcomes have increased. The results in the first cycle were 24.24% of students who had a very high category, in the second cycle it increased by 84.85%, while in the high category it became 15.15%. The increase in learning outcomes in the cognitive aspect can be seen from the percentage of class completeness in the initial conditions of 9%, the first cycle was 45.45% and in the second cycle, it increased to 87.87%, while the increase in the class average value from the initial conditions was 58.00 Cycle I 71.67 in cycle II 76.39. Based on the results of the study it can be concluded that the critical incident strategy